ANALISIS PENGARUH STRUKTUR MODAL DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI SUB SEKTOR ROKOK YANG TERDAFTAR DI BEI PADA TAHUN 2014-2020 - Dwi Ningrum Anindiyah; Maulana Hadi (STIE DWI SAKTI BATURAJA, 2022)
This study discusses the analysis of the effect of Capital Structure (Debt to Equity Ratio) and Liquidity (Current Ratio) on Profitability (Return On Assets) in manufacturing companies in the consumer goods industry sector, the cigarette sub-sector listed on the Indonesia Stock Exchange (IDX). The analytical method used is panel data regression. The results showed that partially Capital Structure / Debt to Equity Ratio had a significant positive effect on Profitability / Return On Assets in manufacturing companies in the consumer goods industry sector, the cigarette sub sector listed on the IDX. Liquidity Variable / Current Ratio had no significant effect on Profitability / Return On Assets in manufacturing companies in the cigarette sub-sector consumer goods industry listed on the IDX. Based on the F test, the value of Fcount > Ftable or 3.66 > 3.39 means that Capital Structure/DER and Liquidity/CR have a significant simultaneous effect on Profitability/ROA in manufacturing companies in the consumer goods industry sector of the cigarette sub-sector listed on the IDX. The value of the coefficient of determination R Square (R2) is 0.226579, this shows that 22% of the contribution from Profitability/ROA in manufacturing companies in the consumer goods industrial sector, the cigarette sub-sector listed on the IDX, can be explained by Capital Structure/DER and liquidity/CR while the remaining 78% can be explained by other variables outside the model.